How Substantial is the Effect of Polyhexamethylene Biguanide (PHMB) Irrigation Solution on a Wound's Biofilm? - Tanaka, Ferdian; Sandakh, Shaza Nathasya; Hananto, Geovan; Pamuji, Maurin A.; Arviansyah, Arviansyah (Riviera Publishing, 2025)
Background: Biofilm as a key component that contributes to the development of chronic wounds can increase the resistance of bacteria to antiseptic solutions. The current standard procedure for wound care involves the use of wound cleansing solutions such as povidone-iodine, chlorhexidine, and normal saline. Each of these solutions has limitations. One of the newer wound cleansing solutions is Polyhexamethylene Biguanide (PHMB). PHMB is known to inhibit the formation and disrupt the structure of biofilm. This study aims to conduct a systematic review and meta-analysis to evaluate the effectiveness of using PHMB as a wound irrigation solution in reducing biofilm in wounds. Methods: PubMed, Mendeley, ScienceDirect, and Cochrane were used as a database using the keywords for the analysis . Further exclusion using PICO criteria left us with 5 studies that met the inclusion criteria. Results: Our findings demonstrated a significant improvement in irrigation with PHMB group compared to the control group (MD= -5.09, 95% CI -8.40 to -1.78, p= 00001, I2= 99%,), there was significant biofilm reduction with the PHMB group compared to the control group (RD= 0.74, 95% CI 0.56 to 0.91, p= 00001, I2= 0%). Conclusion: Compared to standard wound irrigation solutions, PHMB presents several advantages. It acts as a potent bactericidal agent against biofilm-forming microbes, including both Gram-positive (Staphylococcus aureus and MRSA) and Gram-negative bacteria (Pseudomonas aeruginosa). Additionally, PHMB is effective against fungi (Candida albicans), does not induce pain, and is non-toxic to healthy cells and granulation tissue.